A 12-month prospective exploratory study of muscle and fat characteristics in individuals with mild-to-moderate hip osteoarthritis - Aderson Loureiro; Maria Constantinou; Belinda Beck; Rod S. Barrett; Laura E. Diamond (BMC Musculoskeletal Disorders, 2019)
Abstract Background Reductions in lower extremity muscle strength, size and quality and increased fat content have been reported in advanced hip osteoarthritis (OA). Whether these differences are also evident at earlier stages of the disease and the extent to which they might develop over time is unclear. The main purpose of this 12-month exploratory prospective study was to compare changes in muscle and fat characteristics in individuals with mild-to-moderate hip OA and healthy controls. Methods Fourteen individuals with mild-to-moderate symptomatic and radiographic hip OA (n = 9 unilateral; n = 5 bilateral), and 15 healthy controls similar in age and sex without symptoms or radiographic hip OA were assessed at baseline and at 12-month follow-up. Maximal voluntary isometric strength of the hip and knee muscle groups was assessed using an isokinetic dynamometer. Lower extremity lean and fat mass were assessed using dual-energy x-ray absorptiometry, and thigh muscle and fat areas and thigh muscle density were assessed using peripheral quantitative computed tomography. Results Knee extension (p = 0.01), hip extension (p < 0.01), hip flexion (p = 0.03), and hip abduction (p < 0.01) strength, lower extremity lean mass (p < 0.01), thigh muscle area (p = 0.03), and thigh muscle density (p < 0.01) were significantly lower in hip OA compared to controls. Hip extension (p < 0.05), hip flexion (p = 0.03), and hip abduction (p = 0.03) strength significantly declined over the follow-up period in the hip OA group. Conclusions Pre-existing deficits in hip muscle strength in individuals with mild-to-moderate hip OA were accentuated over 12-months, though no changes in symptoms or joint structure were observed. A longer follow-up period is required to establish whether strength deficits drive clinical and structural decline in these patients. Interventions to prevent or slow declines in strength may be relevant in the management of mild-to-moderate hip OA.